2015
DOI: 10.1111/ceo.12534
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and prognosis of eyeball rupture: eye injury vitrectomy study

Abstract: The closed-funnel retinal detachment or extensive retinal loss, PVR-C, and choroidal damage are the risk factors for unfavourable outcomes in globe ruptures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Early RD and subsequent PVR development are not the only dangers threatening these severely injured eyes. Retinal incarceration into the wound (Feng et al, 2015) is a pathology that can lead to total RD within weeks (even if true PVD does not develop), with the entire retina eventually being drawn into the wound and creating a closed funnel. The incarceration can also create a "bridge" across which the proliferating cells populate other parts of the retina (Cleary and Ryan, 1979c), leading to the classical image of endstage PVR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early RD and subsequent PVR development are not the only dangers threatening these severely injured eyes. Retinal incarceration into the wound (Feng et al, 2015) is a pathology that can lead to total RD within weeks (even if true PVD does not develop), with the entire retina eventually being drawn into the wound and creating a closed funnel. The incarceration can also create a "bridge" across which the proliferating cells populate other parts of the retina (Cleary and Ryan, 1979c), leading to the classical image of endstage PVR.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to appreciate that a full-thickness scleral wound (rupture, penetrating or perforating injury) need not have occurred for retinal incarceration to develop: the retina can also be dragged into the site of an IOFB impact if the injury is deep enough to involve the choroid directly (a significant factor in PVR development : Feng et al, 2015). In such cases, fullthickness retinal folds are seen radiating from the lesion ("PVR stage 0"), but no RD is present.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports [26] have suggested that the best prognosis is found for closed ocular injury. In an open eye injury, the prognosis of a perforating injury is better than that of rupture.…”
Section: Discussionmentioning
confidence: 99%
“…However, the timing of surgery is very important. The principle of treatment for patients with ruptured eyeball injury is to suture the wound immediately and restore the integrity of the eyeball as soon as possible [13]. In case of suprachoroidal hemorrhage, vitrectomy is considered about 14 days after the injury.…”
Section: Discussionmentioning
confidence: 99%